Diffuse melanosis cutis secondary to metastatic malignant melanoma: case report - Cheymae Saadani Hassani; Salim Galouj; Safae Zinoune; Ghita Senhaji; Hanane Baybay; Fatima Zahra Mernissi; Samia Arifi; Naoufal Mellas (Our Dermatology Online, 2019)
Diffuse melanosis cutis (DMC) is an exceptional presentation of metastatic melanoma characterized by progressive blue-gray discoloration of the skin and mucous membranes. It attests a generally advanced metastatic tumor extension. We report an additional case of diffuse melanosis associated with widespread cutaneous and visceral metastases from malignant melanoma. The prognosis are poor in patients with diffuse cutaneous melanosis associated with malign melanoma.